Evaluation of Design Consistency on Horizontal Curves for Two-Lane State Roads in Terms of Vehicle Path Radius and Speed - Biljana Maljković; Dražen Cvitanić (The Baltic Journal of Road and Bridge Engineering)
Experimental investigation was conducted on a 24 km long segment of the two-lane state road to collect the driver behavior data. The research involved 20 drivers driving their own cars equipped with the GPS device. Considering the impact of path radius and speed on the side friction demand, the design consistency on horizontal curves was evaluated by determining the margins of safety. The analysis showed that the vehicle path radii were mainly smaller than curve radius, on average for 12%. Regression analysis indicated that the percentage difference between the curve radius and vehicle path radius is not affected by the speed, speed differential and geometric characteristics of the curve and surrounding elements. Two different margins of safety were analyzed. One is the difference between maximum permissible side friction (based on design speed) and side friction demand, while another is the difference between side friction supply (based on operating speed) and side friction demand. Generally, demands exceeded supply side friction factors on curves with radii smaller than 150 m, whereas “poor” conditions (in terms of Lamm’s consistency levels) were noted for curves under approximately 220 m. Both values are very close to the critical radius below which higher accident rates were observed according to several accident studies. Based on the results of the research, it is proposed to use a 12% smaller curve radius for the evaluation of margin of safety and that curves with radii smaller than 200 m should be avoided on two-lane state roads outside the built-up area.